Successful Treatment Of Basal Cell Carcinoma Encroaching The Eyelid With Cryofreeze And Plastic Repair - Kochhar Atul M; Reddy B S N (Wolters Kluwer Medknow Publications, 2001)
Basal cell carcinoma is one of the most common skin cancers encountered in dermatological practice. The case details of a basal cell epithelioma occurring near the left eye in a 42 years old male and its successful treatment with cryofeeze is reported for its clincial interest and therapeutic considerations.